Engineered Platelet‐Derived Growth Factor‐Releasing Hydrogels Promote Fetal Membrane Healing In Vivo. (8th January 2023) - Avilla‐Royo, Eva; Vonzun, Ladina; Seehusen, Frauke; Vallmajo‐Martin, Queralt; Famos, Flurina; Moser, Lukas; Gegenschatz‐Schmid, Katharina; Krattiger, Lisa Amanda; Strübing, Nele; Weisskopf, Miriam; Moehrlen, Ueli; Ochsenbein‐Kölble, Nicole; et al.
Abstract: Fetoscopic interventions to treat fetal anomalies are currently performed for a variety of conditions. Depending on the procedure, preterm rupture of the fetal membranes (FMs) happens in around 30% of the cases, potentially leading to preterm birth and fetal morbidity and mortality. Here, the capacity of modular transglutaminase crosslinked poly(ethylene glycol) (TG‐PEG) hydrogels that release platelet‐derived growth factor (PDGF)‐BB to promote FM healing is described. In vitro, such growth factor‐loaded hydrogels are able to stimulate amniotic cell migration and proliferation. When applied in vivo, these TG‐PEG hydrogels tightly seal the FM and uterus defects created by a fetoscope and remain stable for 10 days. The migration of healing‐related cells into such hydrogels in the myometrium, endometrium, and FM areas is only possible in soft TG‐PEG hydrogels. Importantly, bioengineered hydrogels releasing PDGF‐BB promote recruitment of host cells from the myometrium and the endometrium, and to a lesser extent from FM areas. In such hydrogels, the potent proliferation and matrix production of the recruited cells at the site of treatment into the biomaterial initiates a robust early healing response. PDGF‐BB‐loaded TG‐PEG hydrogels hold great promise for the treatment of fetoscopy‐induced FM defects and for the prevention of preterm birth. Abstract : Treatments to prevent the preterm prelabor rupture of the fetal membranes (FMs) after fetoscopic interventions are currently missing. Here, a growth factor‐releasing biomimetic hydrogel for the preventive healing of FMs is developed. This biomimetic hydrogel seals ovine FM defects and upon growth factor delivery promotes a strong healing response, demonstrating its potential for the healing of defective FMs.